The diversity of classical archaeology - Lichtenberger, Achim; Raja, Rubina (Studies in classical archaeology, 2017)
This book is the first volume in the series Studies in Classical Archaeology, founded and edited by professors of classical archaeology, Achim Lichtenberger and Rubina Raja. This volume sets out the agenda for this series. It achieves this by familiarizing readers with a wide range of themes and material groups, and highlighting them as core areas of traditional classical archaeology, despite the fact that some have hitherto been neglected.00Themes presented in this volume include Greek and Roman portraiture and sculpture, iconography, epigraphy, archaeology, numismatics, the Mediterranean, settlement patterns, landscape archaeology, historiography, and urban archaeology. Additionally, essays on topics such as the early Islamic period and portraiture in the Near East serve to broaden the themes encompassed by this work, and demonstrate the importance of interdisciplinary knowledge in the field. The volume also offers discussions about a variety of material groups, time frames, and regions that have recently come to the fore as areas that should increasingly be considered as belonging to ?and more crucially, informing? classical archaeology. The multi-disciplinary essays contained within this volume, contributed by prominent scholars from across the world, thus represent the status quo of classical archaeology, as well as tracing both how the discipline has developed over time and how it should progress in the future